2018
DOI: 10.1155/2018/2686728
|View full text |Cite
|
Sign up to set email alerts
|

Pinnipeds and PTSD: An Analysis of a Human-Animal Interaction Case Study Program for a Veteran

Abstract: The objective of this study was to examine the impact of a pinniped (grey and harbor seals) facilitated human-animal interaction pilot program on the self-reported PTSD-like symptoms of a veteran. This study analyzed preexisting, deidentified data that represented the participant's scores on the Post-Traumatic Stress Disorder Checklist (PCL-5). The PCL-5 was completed as part of a pilot program operated in partnership between the Veteran and Military Affiliated Research Center (VMARC) and a local aquarium. Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Eight research papers detail the efficacy of interventions (Bracciano et al., 2012; Classen, Cormack, et al, 2014; Classen, Monahan, Canonizado, & Winter, 2014; Krpalek, Achondo, Daher, & Javaherian, 2020; McLaughlin & Hamilton, 2019; Rogers, Mallinson, & Peppers, 2014; Speicher, Walter, & Chard, 2014; Wortman et al., 2018) and two report on occupational performance issues related to military veterans (Dutra, Eakman, & Schelly, 2016; Gregg, Kitzman, & Shordike, 2016). One research paper reported intervention efficacy for military personnel (Beck et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight research papers detail the efficacy of interventions (Bracciano et al., 2012; Classen, Cormack, et al, 2014; Classen, Monahan, Canonizado, & Winter, 2014; Krpalek, Achondo, Daher, & Javaherian, 2020; McLaughlin & Hamilton, 2019; Rogers, Mallinson, & Peppers, 2014; Speicher, Walter, & Chard, 2014; Wortman et al., 2018) and two report on occupational performance issues related to military veterans (Dutra, Eakman, & Schelly, 2016; Gregg, Kitzman, & Shordike, 2016). One research paper reported intervention efficacy for military personnel (Beck et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In two animal‐assisted therapy (AAT) studies, investigators reported improvements in human physical, social, emotional, and cognitive functioning for military veterans (McLaughlin & Hamilton, 2019; Wortman et al., 2018). Wortman et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…208 fulltext studies were assessed for eligibility. We finally included 41 studies (Balluerka, Muela, Amiano, & Caldentey, 2015Beck et al, 2012;Bergen-Cico et al, 2018;Burton, Qeadan, & Burge, 2019;Craven, 2013;Dietz, Davis, & Pennings, 2012;Earles, Vernon, & Yetz, 2015;Faye, 2003;Gehrke, Noquez, Ranke, & Myers, 2018;Gómez, 2016;Hamama et al, 2011;Johnson et al, 2018;Kemp, Signal, Botros, Taylor Whittlesey-Jerome, 2014; Woodward, Jamison, Gala, & Holmes, 2017;Woodwart, Jamison, Gala, & Arsenault, 2017;Woolley, 2004;Wortman et al, 2018;Yarborough et al, 2017;Yorke et al, 2013) (see Figure 1) that were published in 46 reports with 1111 analysed participants. The meta-analysis included eight controlled studies with 469 participants.…”
Section: Search Resultsmentioning
confidence: 99%